Strategi Penyusunan Rencana Kerja dan Anggaran Madrasah (RKAM) dalam Meningkatkan Efektivitas Pengelolaan Pendidikan di MA Al-Ihsan Boarding School (IBS) - Dita Aprilia Hutagaol; Febrian Nur Alim; Imam Ma'rif; Nadia Nabila; Putri Nabila Hutagalung; Rinda Lutfia Kaysa; Tarisa Dwi Tania; Zaskia Adella Ramadhani; Sohiron (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to describe the strategy for preparing the Madrasah Activity and Budget Plan (RKAM) based on the results of the Education Report Card evaluation at MAS Al-Ihsan Boarding School Riau. The method used is descriptive qualitative through observation, interview, and documentation study techniques. The results show that the RKAM preparation process begins with the implementation of Madrasah Self-Evaluation (EDM) conducted every September, involving various stakeholders such as the principal, treasurer, vice principals, administrative staff, operators, and school committee. RKAM has been based on the Education Report Card, where quality evaluation data is used as the basis for determining program and budget priorities. Fund allocation is calculated based on the number of students at IDR 1,500,000 per student per year, which is then distributed according to the operational needs of the madrasah. Monitoring is carried out periodically through weekly, monthly, and semester reports, with supervision from the Ministry of Religious Affairs. Nevertheless, there are still deficiencies in the RKAM document, such as the absence of success indicators, implementation timelines, root cause analysis, and identification of main problems. This study recommends systematic document improvements to continuously improve the quality of planning and budget accountability.